Isolation and Purifi cation of Chitinase Bacillus sp. D2 Isolated from Potato Rhizosfer - Margino, Sebastian; Behar, Chatarina; Asmara, Widya (Indonesian Journal of Biotechnology, 2012)
Potato Cyst Nematodes (Globodera rostochiensis) is one of the important potato’s pests and caused economic looses up to 70% in the several centrals of potato plantations in Indonesia. Potato Cyst Nematodes (PCN) shell component of egg shell containing chitin (inner layer) and vitelline/protein (outer layer), so the purpose of research was to fi nd out of chitin degrading bacteria for controlling of egg’s PCN by cutting of their life cycle. The results showed that Bacillus sp. D2 isolated from potato rhizosphere could produce extra cellular chitinase in the medium containing of 0.20% colloidal chitin and fermented for 72 hours. Result of chitinase purifi cation using ammonium sulphate precipitation and DEAE-Cellulose ion-exchange chromatography showed a specifi c activity 2691,052 U/mg and analyzing using SDS-PAGE 12.5% resulted in molecular weight 30 kDa. The apparent Km and Vmax of chitinase towards colloidal chitin were 2 mg/ml and 2.2 μg/h, respectively.